Effect Anticipation Affects Perceptual, Cognitive, and Motor Phases of Response Preparation: Evidence from an Event-Related Potential (ERP) Study - Harrison, Neil R.; Ziessler, Michael (Frontiers in Human Neuroscience, 2016)
The anticipation of action effects is a basic process that can be observed even for key-pressing responses in a stimulus-response paradigm. In Ziessler, Nattkemper and Vogt’s (2012) experiments participants first learned arbitrary effects of key-pressing responses. In the test phase an imperative stimulus determined the response, but participants withheld the response until a Go-stimulus appeared. Reaction times were shorter if the Go-stimulus was compatible with the learned response effect. This is strong evidence that effect representations were activated during response planning. Here we repeated the experiment using event-related potentials (ERPs), and we found that Go-stimulus locked ERPs depended on the compatibility relationship between the Go-stimulus and the response effect. In general, this supports the interpretation of the behavioural data. More specifically, differences in the ERPs between compatible and incompatible Go-stimuli were found for the early perceptual P1 component and the later frontal P2 component. P1 differences were found only in the second half of the experiment and for long SOAs between imperative stimulus and Go-stimulus, i.e. when the effect was fully anticipated and the perceptual system was prepared for the effect-compatible Go-stimulus. P2 amplitudes, likely associated with evaluation and conflict detection, were larger when Go-stimulus and effect were incompatible; presumably, incompatibility increased the difficulty of effect anticipation. Onset of response-locked LRPs occurred earlier under incompatible conditions indicating extended motor processing. Together, these results strongly suggest that effect anticipation affects all (i.e. perceptual, cognitive, and motor) phases of response preparation.